PENGARUH KEPEMILIKAN MANAJERIAL DAN LEVERAGE TERHADAP MANAJEMEN LABA DENGAN KONVERGENSI IRFS SEBAGAI VARIABEL MODERATING PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Marini Marini (Jurnal Akuntansi Manajerial (Managerial Accounting Journal), 2017)
This research is a study on "The Effect of Managerial Ownership and Leverage to Profit Management Moderated By The IFRS Convergence In Mamufaktur Company Registered in Indonesia Stock Exchange". The dependent variable in this study is Earnings Management, while the independent variable is Managerial Ownership and Leverage. Moderating variables using variable IFRS Convergence. The population was about 130 pmanufaktur company listed in Indonesia Stock Exchange. companies that meet the criteria are as many as 28 companies, so that the data used was 140 Data. The study was conducted with several stages of stages of data collection that meets the criteria, feasibility testing phases of data by using the classical assumption, hypothesis testing phases of the study using multiple regression to test the hypothesis either partially or simultaneously and testing phases of the impact of IFRS convergence moderation, whether strengthen or weaken the effect of managerial ownership variable and Leverage on Earnings Management. The results of this study prove that partial, managerial ownership variable does not significantly influence the management of lava, while leverage significant effect on Earnings Management. Variables simultaneously managerial ownership and leverage significant effect on earnings management, while the convergence of IFRS did not moderate the moderation of managerial ownership on earnings management, but weakens the effect of leverage on earnings management.